EFEKTIVITAS MODEL PROJECT BASED LEARNING PADA MATERI JARINGAN LOKAL DAN INTERNET SISWA SMA - Pitaloka, Diah; Rosita, Dewi (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Project-Based Learning (PjBL) is a learning method that prioritizes hands-on experience in completing projects. The purpose of this study is to determine how effective the use of the PjBL model is to improve students' understanding and learning outcomes on local network and internet material in class X SMA. The research method used was descriptive quantitative, and a pre-experiment design was used (One Group Pretest-Posttest Design). Students were given a pretest before learning, then the PjBL model was applied, and ended with a posttest to measure the improvement of learning outcomes. The study findings stated that before the application of the PjBL model, all students scored below the minimum standard of completeness. After the application of PjBL, 81.25% of students achieved learning completeness with a significant increase in the average score. With a percentage increase of 71.8 percent, the N-Gain analysis showed a score of 0.71, indicating that it was quite effective. In addition, students' activities in learning showed positive engagement with an average of 78.5%, as well as 97.2% of students gave positive responses to this learning process. Therefore, the PjBL model has been proven to successfully improve students' learning outcomes on local network and internet materials.